Philippine cinema, 1897-2020 - Vibal, Gaspar A.; Villegas, Dennis Santos; Co, Teddy O.; Vibal Foundation, Inc. (Quezon City, Philippines Vibal Foundation, 2020)
This lavishly illustrated art book not only provides a dazzling retrospective of over a hundred years of Philippine cinema, it also simultaneously traces its history, genres, narratives, tropes and lore while subjecting its rich filmography to critique and film theory. The book tracks Philippine cinematic beginnings as a technological marvel and its many turns up to the twenty-first century as it blindly accepted, appropriated, indigenized, and even attacked Western conventions through intentionally wicked but hilarious parodies.

The volume also boldly looks at the seamier side of the industry with its unblinking examination of DVD plenitude and piracy, trafficking of low-brow exploitation flicks, dislocation of mainstream distribution brought on by the advent of streaming and Netflix, and the tragic loss of the cinematic archive and the consequent loss of national memory. Nevertheless, a common thread runs through all its pages: a fevered cinephilia that equally valorizes the sublime and the ridiculous, from the socially realistic films set in the most miserable slums to the most inspired satires of sky capers and spaghetti westerns, and from the most profound critique to a weltering list-mania of nostalgia and trivia. Its one hundred essays survey more than 2,000 movies and contain 1,200 notes and gossipy asides, plus over 1,300 images, which will equally delight any diehard movie buff or casual cinematic art lover.
Includes bibliographical references (pages 381-387) and index (pages 388-408).
In English.
Winner, National Book Awards, National Book Development Board.
Keywords: Motion pictures -- Social aspects -- Philippines; Motion pictures -- Philippines -- History and criticism